Antinociceptive and anti-inflammatory effects of Sida rhombifolia L. in various animal models. - Sulaiman, Mohd Roslan; Moin, Saidi; Alias, Ashraf S.; Zakaria, Zainul Amiruddin (Medwell Publishing, 2008)
The present study was carried out to determine the antinociceptive and anti-inflammatory activities of the ethanolic extract of Sida rhombifolia L. leaves in various animal models. The antinociceptive activity was measured using the abdominal constriction test and hot plate test, while the anti-inflammatory was assessed using the carrageenan-induced paw edema test. The dried leaves of S. rhombifolia was mixed with 95% ethanol (1: 10; w/v), incubated in water bath (55°C) for 72 h, filtered and evaporated to dryness (50°C) under reduced pressure. The sticky paste of extract was then emulsified using 0.1% Tween-80 in normal saline at concentrations required to produce doses of 30, 100 and 300 mg kg-1 body weight. Based on the data obtained, all doses of the extract, administered intraperitoneally, exhibited significant (p<0.05) antinociceptive and anti-inflammatory activities in a dose-dependent manner. In conclusion, the leaves of S.rhombifolia possessed antinociceptive and anti-inflammatory activities and confirms its traditional uses in the treatment of pain-and inflammatory-related ailments.